The Role of Teachers of Teachers in Online Learning with the Google Classroom Platform (Multicase Study of Middle School in Tulungagung) - Sukisworo, Fetri; Marsono, Marsono; Widiyanti, Widiyanti (Budapest International Research and Critics University, 2021)
The COVID-19 pandemic has had a fundamental impact on the joints of mankind. Starting from health, this pandemic attacks the realm of education. The enactment of regulations by maintaining a distance of approximately one meter has consequences for the education process in Indonesia, requiring elements of education to conduct a distance learning process. This term is holding online learning as a substitute for face-to-face methods to keep it held, namely in the internet network. The implementation of the 2013 curriculum in several schools in Indonesia has an impact on the readiness and role of teachers in the online learning process, one of which is following the new provisions concerning the Regulation of the Minister of Education and Culture Number 68 of 2014 concerning the Role of Information and Communication Technology (ICT) Teachers in the implementation of the 2013 curriculum. as an ICT guidance teacher in schools, including the high school in Tulungagung. The application of distance learning that uses technology in learning or e-learning creates an internet connection as well as information technology learning management system services that support the online learning process, namely Google Classroom. In this paper, the researcher focuses on the role of ICT guidance teachers in online learning using Google Classroom.